2020
DOI: 10.3389/fpsyg.2020.01699
|View full text |Cite
|
Sign up to set email alerts
|

Codeswitching: A Bilingual Toolkit for Opportunistic Speech Planning

Abstract: The ability to engage in fluent codeswitching is a hallmark of the flexibility and creativity of bilingual language use. Recent discoveries have changed the way we think about codeswitching and its implications for language processing and language control. One is that codeswitching is not haphazard, but subject to unique linguistic and cognitive constraints. Another is that not all bilinguals codeswitch, but those who do, exhibit usage patterns conforming to community-based norms. However, less is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 97 publications
1
35
0
Order By: Relevance
“…Quantitative analysis of these data has revealed the systematicity underlying codeswitching tendencies by exemplifying bilinguals' adherence to community norms over idiosyncratic behaviors (Poplack 1980(Poplack , 1987Poplack and Meechan 1998;Travis 2015, 2018). We have come to see that codeswitching is not random between-language interference but rather serves as an opportunistic strategy 5 that provides communicative precision (Beatty-Martínez et al 2020a;Feldman et al 2021;Xu et al 2021aXu et al , 2021b.…”
Section: Language Cooperationmentioning
confidence: 99%
“…Quantitative analysis of these data has revealed the systematicity underlying codeswitching tendencies by exemplifying bilinguals' adherence to community norms over idiosyncratic behaviors (Poplack 1980(Poplack , 1987Poplack and Meechan 1998;Travis 2015, 2018). We have come to see that codeswitching is not random between-language interference but rather serves as an opportunistic strategy 5 that provides communicative precision (Beatty-Martínez et al 2020a;Feldman et al 2021;Xu et al 2021aXu et al , 2021b.…”
Section: Language Cooperationmentioning
confidence: 99%
“…Codeswitching can be cognitively demanding, and costs can vary with immediacy of the switch (Gullifer & Titone, 2019). Others have suggested that its cost may be offset by optimizing another aspect of communication (Beatty-Martínez et al, 2020). For example, reduced lexical diversity, like other variants of style matching (Abney, Paxton, Dale & Kello, 2014), can be a marker of better cooperation among speakers (Feldman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to conditions associated with a codeswitch, we ask whether lexical diversity for English before a codeswitch out of English (and into Spanish) and after a codeswitch (from Spanish) into English is greater than in tweets remote (± 10 tweets) from a codeswitch. Differentiated word usage would suggest that communicative precision at a codeswitch as indexed by vocabulary richness creates an opportunity that attenuates constraints against mixing languages (Beatty-Martínez, Navarro-Torres & Dussias, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the EF tasks used, Grote et al’.s study (2021) provides a promising methodological framework for assessing EFs in bilingual children, which, if combined with measurements of language usage patterns, could reveal insights into the causes of bilingualism effects on EF development. The Adaptive Control Hypothesis suggests that one of the key factors influencing EFs in bilinguals is code-switching, that is, the common bilingual practice of switching between languages within the same utterance or conversation to optimise communication in bilingual contexts (Beatty-Martínez et al, 2020; Green & Abutalebi, 2013). Indeed, there is growing evidence that code-switching in adult bilinguals modulates EFs (Hofweber et al, 2020; Lai & O’Brien, 2020; Verreyt et al, 2016; Yang et al, 2016) and divergent thinking (Kharkhurin & Wei, 2015), although counter-examples and null-results co-exist (Paap et al, 2017).…”
Section: Exploring the Causes Underlying The Observed Effects Of Bilingualism On Executive Functionsmentioning
confidence: 99%